Cyano-Functionalized Porphyrins on Cu(111) from One-Dimensional Wires to Two-Dimensional Molecular Frameworks: On the Role of Co-Deposited Metal Atoms - Dos Santos, Alisson Ceccatto; De Campos Ferreira, Rodrigo Cezar; Moreno-Lopez, Juan Carlos; Barreto, Lucas; Lepper, Michael; Landers, Richard; Steinrück, Hans-Peter; Marbach, Hubertus; De Siervo, Abner (Chemistry of Materials, 2020)
Metal adatoms play a key role in surface diffusion, adsorption conformation, and self-assembly of porphyrin molecules on metal surfaces. Herein, we study the specific influence of coadsorption of Fe, Co, and Pd atoms on the behavior of 2H-tetrakis(p-cyano)phenylporphyrin (2H-TCNPP) on Cu(111) using scanning tunneling microscopy. Upon co-deposition of Fe and Co, the molecules form one-dimensional (1D) linear chains after mild annealing on Cu(111) driven by the interaction of its cyano groups with metal adatoms. A similar behavior has been observed previously on Cu(111), mediated by Cu adatoms, where the functional CN groups were also found to lower the reaction rate of the so-called porphyrin self-metalation reaction with Cu atoms significantly, in comparison to the non-cyano-functionalized porphyrin. Upon co-deposition of Pd and mild annealing, we find a remarkably different behavior, that is, a massive reorganization from 1D molecular chains to a peculiar rectangular 2D (two-dimensional) network. The molecular appearance changes to a clover shape, which is attributed to a Pd-induced dehydrogenation and subsequent ring closure reaction of the phenyl and pyrrole groups.
CRIS-Team Scopus Importer:2020-03-27